Identification and prevention of microbial contaminants in Musa paradisiaca tissue culture - Nurul Izzah Hassen,; Noor Afiza Badaluddin,; Zakiah Mustapha,; Dhiya Dalila Zawawi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Banana (Musa spp.) is an economically vital fruit crop in Malaysia and therefore, micropropagation was applied to meet the market demand for disease-free seedlings. However, microbial contamination is a significant obstacle in micropropagation techniques. In this research, the microorganisms that were present in the banana culture were characterized and the efficacy of antimicrobial and antifungal agents to inhibit contaminants was evaluated. Three bacterial and two fungal isolates were isolated from the contaminated culture. Klebsiella pneumoniae, Klebsiella quasipneumoniae, and Klebsiella variicola were identified by molecular identification based on the 16S rDNA sequence. The gram-staining method confirmed all three bacteria were gram-negative. Oxidase and catalase tests showed the presence of cytochrome oxidase system and catalase enzyme in all bacteria. The bacteria can also hydrolyze starch, ferment sugars, and reduce sulfur from the amylase test. Phenotypic identification of fungi revealed the presence of conidia and hyphae, indicating the presence of Colletotrichum spp. and Aspergillus spp. In fungi characterization, Colletotrichum gloeosporioides and Aspergillus flavus were detected. Chloramphenicol was identified as an effective antibacterial agent from the disc diffusion method. Fluconazole was a potent antifungal agent by screening the sterilizing agents. The findings may potentially lead the way for the implementation of reducing the contamination rate in banana micropropagation.